The Antibacterial Peptides (AMPs) Originated from Tryptic Hydrolysis of Naja sumatrana Venom Fractionated Using Cation Exchange Chromatography - Ahmed, Naseer; Raharjo, Slamet; Swasono, Respati Tri; Raharjo, Tri Joko (Rasayan Journal of Chemistry, 2022)
Bioactive peptides bring revolutions in the medical field and become an attractive target for new antibiotics. The bioactive peptides can be derived from the hydrolysis of protein. This study aims to explore the antibacterial peptide from venom hydrolysate of the Spitting cobra (Naja sumatrana). The venom protein was isolated from venom using a gel filtration technique. The digestion of venom protein was performed using trypsin with and without alkylation and reduction. After that, fractionation was carried out using a strong cation exchange solid-phase extraction, followed by antibacterial activity testing. The active peptides present in the active fractions were identified using HRMS. The protein hydrolysis with pretreatment using alkylation and reduction gave almost two-fold higher than that of untreated hydrolysis. Both the venom protein and the hydrolysate showed antibacterial activity against Escherichia coli but there was no activity against Staphylococcus aureus. Antibacterial activity has been detected in numerous cation exchange fractions against Escherichia coli and Staphylococcus aureus. The four best bioactive peptides were identified with amino sequences of VYGGDSR, YTPTNK, TQFSDR, and TFQDSR. In addition, molecular docking analysis revealed that the peptides showed high-affinity scores, and the model best matched the DNA gyrase subunit B by salt bridge formation, whereas hydrogen bond interactions proved inhibition of bacterial replication as an antibacterial mechanism.